An unusual case of epidermodysplasia verruciformis with mild cutaneous involvement and extensive genital cancers - Sałkowska-Wanat, Joanna M.; Trzeciak, Leszek; Smolarczyk, Katarzyna; Pniewski, Tomasz; Płoski, Rafał; Majewski, Sławomir (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction. Human papillomaviruses (HPV) consist of more than 120 subtypes of viruses, which can be divided into three main groups: skin subtypes, mucosal subtypes and types responsible for the occurrence of the skin lesions in autosomal recessive disorders such as epidermodysplasia verruciformis . Objective . The aim of the study was to evaluate the correlation between the occurrence of epidermodysplasia verruciformis and the development of genital cancers. Case report. We analyzed the case of a young woman suffering from epidermodysplasia verruciformis from 6 years of age, who at the age of 20 developed genital cancers with a severe clinical course resulting in amputation of the uterus, cervix, the top of the vagina and labia major and minor. In the patient we found a mutation in the EVER2 gene and we revealed the presence of EV-HPV type 5, 9, 17, and 20 in unusual genital locations associated with genital cancers. Conclusions . It is possible that in the presented case the rapid and severe course of genital cancers was related to mutation in the EVER2 gene.